Comparison between Male and Female in Best Management Practices for Tobacco Cultivators in Bachok District, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
Kelantan State recorded the highest in terms of acreage for tobacco plantation with consists of 77.94 %. Tobacco plantation was known to be the most risky job among Kelantanese due to extensive usage of pesticide and fertilizer. This study was conducted to identify the differences between male and female in Best Management Practices (BMPs) for tobacco cultivators in Bachok as well as to relate it with the fertilizers and pesticides related diseases in Bachok District, Kelantan, Malaysia. The results revealed that, the correlation between wearing proper PPEs and gender (p
Keywords: Personnel Protective Equipment (PPEs); Best Management Practices (BMPs); tobacco planters; Bachok District; chemicals; health cases